Individual, generalized, and moderated effects of the good behavior game on at-risk primary school students: A multilevel multiple baseline study using behavioral progress monitoring - Leidig, Tatjana; Casale, Gino; Wilbert, Jürgen; Hennemann, Thomas; Volpe, Robert J.; Briesch, Amy; Grosche, Michael (Frontiers in Education, 2022)
The current study examined the impact of the Good Behavior Game (GBG) on the academic engagement (AE) and disruptive behavior (DB) of at-risk students’ in a German inclusive primary school sample using behavioral progress monitoring. A multiple baseline design across participants was employed to evaluate the effects of the GBG on 35 primary school students in seven classrooms from grade 1 to 3 (Mage = 8.01 years, SDage = 0.81 years). The implementation of the GBG was randomly staggered by 2 weeks across classrooms. Teacher-completed Direct Behavior Rating (DBR) was applied to measure AE and DB. We used piecewise regression and a multilevel extension to estimate the individual case-specific treatment effects as well as the generalized effects across cases. Piecewise regressions for each case showed significant immediate treatment effects for the majority of participants (82.86%) for one or both outcome measures. The multilevel approach revealed that the GBG improved at-risk students’ classroom behaviors generally with a significant immediate treatment effect across cases (for AE, B = 0.74, p < 0.001; for DB, B = –1.29, p < 0.001). The moderation between intervention effectiveness and teacher ratings of students’ risks for externalizing psychosocial problems was significant for DB (B = –0.07, p = 0.047) but not for AE. Findings are consistent with previous studies indicating that the GBG is an appropriate classroom-based intervention for at-risk students and expand the literature regarding differential effects for affected students. In addition, the study supports the relevance of behavioral progress monitoring and data-based decision-making in inclusive schools in order to evaluate the effectiveness of the GBG and, if necessary, to modify the intervention for individual students or the whole group.